2022
DOI: 10.3389/fnins.2022.915405
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Dysfunction in Diverse Communities With Health Disparities—Contributions to Dementia and Alzheimer’s Disease

Abstract: Alzheimer’s disease and related dementias (ADRD) are an expanding worldwide crisis. In the absence of scientific breakthroughs, the global prevalence of ADRD will continue to increase as more people are living longer. Racial or ethnic minority groups have an increased risk and incidence of ADRD and have often been neglected by the scientific research community. There is mounting evidence that vascular insults in the brain can initiate a series of biological events leading to neurodegeneration, cognitive impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 346 publications
0
7
0
Order By: Relevance
“…A small percentage of all Alzheimer's disease (AD) cases, the most common type of dementia, are autosomal-dominant AD (ADAD) caused by known mutations in Presenilin-1 (PSEN1), Presenilin-2 (PSEN2), and Amyloid protein precursor (APP) genes. 29 Most AD cases are sporadic, without a primary genetic cause. However, numerous genome-wide association studies have identified genetic risk factors associated with sporadic AD.…”
Section: State Of the Sciencementioning
confidence: 99%
See 4 more Smart Citations
“…A small percentage of all Alzheimer's disease (AD) cases, the most common type of dementia, are autosomal-dominant AD (ADAD) caused by known mutations in Presenilin-1 (PSEN1), Presenilin-2 (PSEN2), and Amyloid protein precursor (APP) genes. 29 Most AD cases are sporadic, without a primary genetic cause. However, numerous genome-wide association studies have identified genetic risk factors associated with sporadic AD.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Most AD cases are sporadic, without a primary genetic cause. However, numerous genome‐wide association studies have identified genetic risk factors associated with sporadic AD 29 . These studies largely encompassed Europeans or Americans of European descent, and repeatedly identify apolipoprotein E (APOE) ε4 as the greatest genetic risk factor for sporadic AD 30 .…”
Section: Non‐modifiable Risk Factors Contributing To Adrd Burden In R...mentioning
confidence: 99%
See 3 more Smart Citations